2018
DOI: 10.3389/fncel.2018.00034
|View full text |Cite
|
Sign up to set email alerts
|

The Fly Sensitizing Pigment Enhances UV Spectral Sensitivity While Preventing Polarization-Induced Artifacts

Abstract: Microvillar photoreceptors are intrinsically capable of detecting the orientation of e-vector of linearly polarized light. They provide most invertebrates with an additional sensory channel to detect important features of their visual environment. However, polarization sensitivity (PS) of photoreceptors may lead to the detection of polarization-induced false colors and intensity contrasts. Most insect photoreceptors are thus adapted to have minimal PS. Flies have twisted rhabdomeres with microvilli rotated alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…To verify the efficacy of this stimulus presentation system, we have characterized the stimuli emanating from our apparatus using a polarimetric camera 27 (Figure 3B). By calculating the degree of linear polarization as previously described 27 , we confirm that the polarized stimuli manifest a high degree of polarization both in the UV (365 nm) as well as with a green LED (510 nm). In contrast, virtually no polarization is detected when the polarization filter / diffuser combination of the upper filter cassette is inverted.…”
Section: Characterization Of the Visual Stimulussupporting
confidence: 70%
“…To verify the efficacy of this stimulus presentation system, we have characterized the stimuli emanating from our apparatus using a polarimetric camera 27 (Figure 3B). By calculating the degree of linear polarization as previously described 27 , we confirm that the polarized stimuli manifest a high degree of polarization both in the UV (365 nm) as well as with a green LED (510 nm). In contrast, virtually no polarization is detected when the polarization filter / diffuser combination of the upper filter cassette is inverted.…”
Section: Characterization Of the Visual Stimulussupporting
confidence: 70%
“…We have previously shown that the contrast between the polarized patterns reflected from fur or water and the surrounding visual clutter is optimal in the UV- and blue-wavelength range (60). This has most likely driven the evolution of horsefly VPV to employ UV- and blue-sensitive photoreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical data were used to calculate the PS A as an estimate of the physiological photoreceptor PS. The calculations were based on a discrete model (60), modified from ref. 42.…”
Section: Methodsmentioning
confidence: 99%